Moderasi Beragama di Era Milenial - Fatmah, Nirra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This article discusses religious moderation in the millennial era. The purpose of this article is to add insight into the understanding, application, and impact of religious moderation in the millennial era. The author uses a qualitative research method that aims to provide a complete and comprehensive description of social reality and various phenomena of the object of research that occur in society, thus forming the characteristics, characters, and models of these phenomena. Data collection techniques: observation, interviews and documentation. Data analysis was then carried out with descriptive analytical methods to draw conclusions about religious moderation in the millennial era. The results showed that 1. The level of understanding and application of the concept of religious moderation in the millennial era has not fully understood the meaning and concept of religious moderation. However, they have been able to apply or implement religious moderation in their daily lives. 2. The impact of technological developments and social media on religious moderation in the millennial era, almost all millennials have understood the positive and negative impacts of using technology and social media on religious moderation.